Understanding the Biology of Antigen Cross-Presentation for the Design of Vaccines Against Cancer - Fehres, Cynthia M.; Unger, Wendy W. J.; Garcia-Vallejo, Juan J.; van Kooyk, Yvette (Frontiers in Immunology, 2014)
Antigen cross-presentation, the process in which exogenous antigens are presented on MHC class I molecules, is crucial for the generation of effector CD8+ T cell responses. Although multiple cell types are being described to be able to cross-present antigens, in vivo this task is mainly carried out by certain subsets of dendritic cells (DCs). Aspects such as the internalization route, the pathway of endocytic trafficking, and the simultaneous activation through pattern-recognition receptors have a determining influence in how antigens are handled for cross-presentation by DCs. In this review, we will summarize new insights in factors that affect antigen cross-presentation of human DC subsets, and we will discuss the possibilities to exploit antigen cross-presentation for immunotherapy against cancer.